Immunotherapy Targeting CCR8+ Regulatory T Cells Induces Antitumor Effects via Dramatic Changes to the Intratumor CD8+ T Cell Profile - Ueyama, Azumi; Nogami, Wataru; Nashiki, Kunitaka; Haruna, Miya; Miwa, Hiroto; Hagiwara, Masaki; Nagira, Morio; Wada, Hisashi; Nagira, Yoji (The Journal of immunology (1950), 2023)
Regulatory T cells (Tregs) contribute to the formation of a tumor-immunosuppressive microenvironment. CCR8 is reportedly selectively expressed in tumor Tregs, and an anti-CCR8 Ab can exert potent antitumor effects by eliminating intratumor Tregs in murine tumor models. In this study, we analyzed changes to intratumor immunity after anti-CCR8 Ab administration, especially in CD8+ T cells, which are involved in cancer cell killing, using the CT26 colorectal carcinoma mouse model. Immunophenotyping of tumor-infiltrating cells by mass cytometry after Ab administration on day 5 of tumor inoculation revealed that CD8+ T cell subsets were dramatically altered in the CCR8 Ab–treated group, with an increase in naive cells and nonexhausted effector cells and a decrease in exhausted cells with high expression levels of TOX. These results were corroborated with flow cytometry analysis. Delayed administration of the anti-CCR8 Ab on day 9 or 12, when the amount of CCR8+ Tregs and CD8+ T cell exhaustion were more progressed, also resulted in a decrease in exhausted CD8+ T cells, leading to tumor regression. Finally, we confirmed that high CCR8+ Treg infiltration was associated with high TOX expression in CD8+ T cells in human cancer patients. In conclusion, administration of an anti-CCR8 Ab can dramatically alter the activation and exhaustion state of intratumor CD8+ T cells, resulting in strong antitumor effects. In cancer patients with an advanced tumor-immunosuppressive environment, CD8+ T cell exhaustion has progressed along with CCR8+ Treg induction. Therefore, targeted depletion of CCR8+ Tregs is expected to be effective in these patients.